(3HQD SGYIs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s ((3OGQ GdTaGA HeUQ GdeMQhSI s)
(3ChdgG (B:s
(3bGd cfJ YfO GdhRjQ CHj GdbGSe Hf YHO Gddg jhekG aLQi HMVQJg PcQ TF ef GdWH aSCdfi GdhRjQ Cf Chda ai Pdc cJGHkG jTJed Ydi LejY GdYdd hGLJgOJ ajg s
(3BNQgG (B:s
(3GdHGH GdQGHY hGdYTQjf ai GdGWQGa EPG YQV dgG GdMcI ai GdTJGA EP gh ZSd jOjg HGdeGA GdHGQO Je cJGH HQD SGYI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOSs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs